Low fatigue lead zirconate titanate-based capacitors modified by manganese for nonvolatile memories - Zhang, Qi; Whatmore, Roger W. (Elsevier, 2004)
We have investigated the effects of Mn doping on the ferroelectric properties of Pb(Zr0.3Ti0.7)O3 (PZT) thin films on substrates Pt/Ti/SiO2/Si. Small amount of Mn-doped (≤1 mol%) PZT (PMZT) showed almost no hysteretic fatigue up to 1010 switching bipolar pulse cycles, coupled with excellent retention properties. We present evidence that while a low permittivity interfacial layer forms between the Pt electrode and PZT films, this does not occur in PMZT. We propose that Mn dopants are able to reduce oxygen vacancy mobility in PZT films and Mn2+ ions consume the oxygen vacancies generated during repeated switching, forming Mn4+ ions. These mechanisms are probably responsible for their low observed fatigue characteristics.